Analisis Konsep Dasar: Pengakhiran Letter of Intent Antara Indonesia-Norwegia dalam Kerjasama REDD+ - Rahmadan, Yanuar (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 1 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONALDO - 10.24843/JIWSP.2023.v05.i01.p03, 2023)
The press release from Indonesian government to end the REDD+ cooperation with the Norwegian government on 10 September 2021 has put Indonesia in question whether the government is ready to threaten their commitment to lower the green house emission from deforestation and forest degradation. Discourses emerged from the official press release as well as on media to mention the end of the cooperation. By using the basic concept methodology and further investigated using the regime effectiveness concept, this study aims to investigate the discourse emerged during the earlier period of the announcement. It is found that the discourse of emission resulted from energy is absent although it becomes the biggest contributor. Moreover, it is also found that the end the partnership is caused by the Norwegian government did not conform to the regime effectiveness concept despite the Indonesian government has fulfilled the target and requirements set earlier during the agreement.